1982
DOI: 10.1128/iai.37.2.499-505.1982
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune response to oral microorganisms in periodontitis

Abstract: Serum antibody titers from patients with periodontitis were compared with those from periodontally healthy subjects. With the micro-enzyme-linked immunosorbent assay, immunoglobulin G (IgG), IgA, and IgM antibody titers to isolates of Streptococcus sanguis, Actinomyces viscosus, Bacteroides gingivalis, Bacteroides melaninogenicus subsp. intermedius, Bacteroides ochraceus, and Fusobacterium nucleatum were determined. Antibody titers of the IgG and IgA classes to B. melaninogenicus, B. ochraceus, F. nucleatum, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
39
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 31 publications
8
39
0
Order By: Relevance
“…Eor practical reawas observed in this study. Similar observa-sons, a simpler test based on 2 or 3 bacteria tions were reported from a small group of may be preferable, and as shown in this healthy adults by Doty et al (1982). In study the sensitivity and specificity were still contrast, Mannsheim et al (1980) observed satisfactory.…”
Section: Discussionsupporting
confidence: 78%
“…Eor practical reawas observed in this study. Similar observa-sons, a simpler test based on 2 or 3 bacteria tions were reported from a small group of may be preferable, and as shown in this healthy adults by Doty et al (1982). In study the sensitivity and specificity were still contrast, Mannsheim et al (1980) observed satisfactory.…”
Section: Discussionsupporting
confidence: 78%
“…Our initial trial to estimate the level of antibodies against fimbriae by an enzyme-linked immunosorbent assay, a quantitative assay, also showed a similar tendency (data not shown). The relation between age and the levels of antibodies against fimbriae should be elucidated to confirm the present notion because of the difference of mean age between HI and AP groups, although we take note of reports stating that no significant changes in the mean levels of antibodies against oral microorganisms including B. gingivalis were observed (1,14). In contrast, antibodies against the type 1 fimbriae of Escherichia coli are known to be commonly present in human sera from adults without dysentery (2).…”
supporting
confidence: 66%
“…In the present study, IgG concentrations towards a specific gingivitis pathogen, A. viscosus, increased (in 5 of 6 subjects) in the healthy post-treatment period compared to the pretreatment gingivitis period. This is in accordance with Doty et al (1982) who reported increased serum antibody titers to certain periodontopathic bacteria in healthy controls compared to diseased subjects. They concluded that in diseased tissues, antibodies may be consumed by interaction with antigens in excess, thus lowering the local antibody concentration.…”
Section: Discussionsupporting
confidence: 93%